Validation of the no presential teaching evaluation instrument in Vocational Training. - Racero Montes, Francisco J.; Ramos Corpas, Manuel Jesús; Castillo García, Manuel (IJERI: International Journal of Educational Research and Innovation, 2021)
The COVID-19 pandemic seriously threatens the health of humanity, causing all types of consequences. The education sector is one of the most affected. Student learning has been reduced in the last quarter of the 2019-20 school year, and if science doesn't find a quick solution to fight the virus, the teaching methods that have had to be forced during this time will likely have to be repeated over the next year. In this context, public administrations within the framework of their constitutional powers are developing different educational models so that each teaching center, thanks to its autonomy, chooses the best option according to the type of education they offer and the different educational levels they develop. The objective of this study has been to develop a valid and reliable instrument to evaluate teaching practice in times of pandemic. The methodological approach corresponds to a cross-sectional research survey of a quantitative nature. The different results of Cronbach's alpha values are offered, as well as a series of descriptive statistics. The factorial structure of this scale is analyzed by exploratory factor analysis, confirmatory analysis using a sample of 329 teachers. The studies carried out show that the scale is made up of six factors: student-teacher attitude index, attention to diversity, teacher coordination index, virtual efficiency index, orientation and tutoring index, virtual teaching practice index.